Making heretics : militant Protestantism and free grace in Massachusetts, 1636-1641 - Winship, Michael P. (Michael Paul) (Princeton University Press, 2002)
"Making Heretics is a new narrative of the famous Massachusetts disputes of the late 1630s misleadingly labeled the "antinomian controversy" by later historians. Drawing on an unprecendented range of sources, Michael Winship fundamentally recasts these interlocked religious and political struggles as a complex ongoing interaction of personalities and personal agendas and as a succession of short-term events with cumulative results." "Previously neglected figures like Sir Henry Vane Wheelright assume leading roles in the processes that nearly ended Massachusetts, while more familiar "hot Protestants" like John Cotton and Anne Hutchinson are relocated in larger frameworks. The book features a striking portrayal of the minister Thomas Shepard as an angry heresy-hunting militant, helping to set the volatile terms on which the disputes were conducted and keeping the flames of contention stoked even as he ostensibly attempted to quell them."--Jacket